1974
DOI: 10.1177/030098587401100605
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulosclerosis in Canine Heartworm Infection

Abstract: Abstract. The kidneys of seven dogs with natural infections of heartworm disease, four dogs with experimental infections, and six control (uninfected) dogs raised in isolation were examined by light, fluorescent, and electron microscopy. Swelling and fragmentation of the basement membranes accompanied by denudations of endothelial cells and fusion and atrophy of foot processes occurred in the glomeruli of dogs with heartworm disease, but not in control dogs. The severity of tissue damage correlated with the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 2 publications
1
4
0
1
Order By: Relevance
“…The glomerular lesions were considered to represent an immune complex form of glomerulonephritis induced by the D. immitis infection. By contrast, another report [76] considered that the renal lesion in dirofilariasis was a glomerulosclerosis with swelling and fragmentation of the basement membranes accompanied by denudations of endothelial cells with fusion and atrophy of foot processes. The severity of tissue damage was correlated with the degree of microfilaremia.…”
Section: Clomerulonephritis In Dogsmentioning
confidence: 92%
“…The glomerular lesions were considered to represent an immune complex form of glomerulonephritis induced by the D. immitis infection. By contrast, another report [76] considered that the renal lesion in dirofilariasis was a glomerulosclerosis with swelling and fragmentation of the basement membranes accompanied by denudations of endothelial cells with fusion and atrophy of foot processes. The severity of tissue damage was correlated with the degree of microfilaremia.…”
Section: Clomerulonephritis In Dogsmentioning
confidence: 92%
“…CROWELL et al (1978) described interstitial nephritis and pyelonephritis in 27% of coyotes infected with D. immitis as compared to a 2% incidence in noninfected coyotes from the same area. A clearer association between interstitial nephritis and D. immitis infections was recently described by SHIEOTA et al, (1979) Demonstrable antigen-antibody complexes were not found in glomeruli of dogs infected with D. immitis with characteristic ultrastructural changes (SIMPSON et al, 1975). These authors suggest that the observed changes are mechanically induced by the microfilaria.…”
Section: Discussionmentioning
confidence: 68%
“…Numerous studies of other host species have also demonstrated that pathological changes occur in other tissues of animals infected with filariae. Of particular interest is the possibility that filariae may induce systemic reactions such as glomerulonephritis (SIMPSON et al, 1972;KLEI et al, 1974), amyloidosis (KLEI et al, 1974;CROWELL et al, 1973;CROVVELL & VOTAVA, 1975), and granuloma formation in various tissues (AH & THOMPSON, 1973;DUKE, 1960;MALONE et al, 1976;WEBB et al, 1960). The present paper reports on kidney, liver, and spleen lesions that have not previously been described in detail or from large numbers of jirds with B. pahangi infections.…”
Section: Introductionmentioning
confidence: 74%
“…Prominent proteinuria has been reported to occur in a low percentage of dogs infected with D. imm i f i~.~~.~~ The glomerular lesion responsible for the proteinuria is reported to be either an immunecomplex membranous g l~m e r u l o p a t h y l~~~~ or a mechanical injury caused by microfilaria. 16 When the urine electrophoretogram was compared to that ,from serum, a preferential loss of albumin relative to globulin in the urine was apparent in this case. Since no microfilaremia occurred in this animal, an immune-complex glomerulonephritis may have been responsible for the proteinuria.…”
Section: Discussionmentioning
confidence: 78%